Dramatic Response of Familial Majeed Syndrome to Interleukin-1 Antagonist Therapy: Case report - Zakiya AL MOSAWI,; Wafa MADAN,; Barrak AL MOOSAWI,; Sayed AL-WADAEI,; Husain NASER,; Fuad ALI, (Archives of Rheumatology, 2019)
Majeed syndrome (MS) is a rare, autosomal recessive, autoinflammatory disease characterized by recurrent multifocal osteomyelitis, congenital dyserythropoietic anemia, and inflammatory dermatome. In this article, we report the cases of two siblings with MS. Genetic studies of both siblings were obtained and revealed mutations in LPIN2 gene by means of a homozygous single-base pair change in the donor splice site of exon 17 (c.2327+1G>C). Both patients underwent different modalities of treatment for MS which involved immune-suppressive and biologic therapies. We observed a significant clinical response to biologic anti-interleukin-1 (IL-1) therapy in our patients. This impressive clinical response indicates the pivotal role of IL-1 in MS pathogenesis. There are limited data on the use of anti-IL-1 therapy in treating MS due to the rarity of the condition. Anti-IL-1 therapy should be considered as a promising treatment for this disease.